2019
DOI: 10.1111/apha.13249
|View full text |Cite
|
Sign up to set email alerts
|

Proteasuria—The impact of active urinary proteases on sodium retention in nephrotic syndrome

Abstract: Sodium retention and extracellular volume expansion are typical features of patients with nephrotic syndrome. In recent years, from in vitro data, endoluminal activation of the epithelial sodium channel (ENaC) by aberrantly filtered serine proteases has been proposed as an underlying mechanism. Recently, this concept was supported in vivo in nephrotic mice that were protected from proteolytic ENaC activation and sodium retention by the use of aprotinin for the pharmacological inhibition of urinary serine prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
47
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 77 publications
3
47
0
3
Order By: Relevance
“…Conventional diuretics, that is, loop diuretics and thiazides, show reduced efficacy in this condition emphasizing the need for a diuretic intervention based on causal understanding. Contrary to the classical view of altered fluid distribution second to a low plasma oncotic pressure, accumulating evidence suggest that oedema formation in NS is because of the aberrant renal sodium retention . It has been shown that pharmacologic blockade of the epithelial sodium channel (ENaC) using amiloride can prevent sodium retention and relieve nephrotic oedema in both rats, mice and humans .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Conventional diuretics, that is, loop diuretics and thiazides, show reduced efficacy in this condition emphasizing the need for a diuretic intervention based on causal understanding. Contrary to the classical view of altered fluid distribution second to a low plasma oncotic pressure, accumulating evidence suggest that oedema formation in NS is because of the aberrant renal sodium retention . It has been shown that pharmacologic blockade of the epithelial sodium channel (ENaC) using amiloride can prevent sodium retention and relieve nephrotic oedema in both rats, mice and humans .…”
mentioning
confidence: 96%
“…Contrary to the classical view of altered fluid distribution second to a low plasma oncotic pressure, accumulating evidence suggest that oedema formation in NS is because of the aberrant renal sodium retention. 4 It has been shown that pharmacologic blockade of the epithelial sodium channel (ENaC) using amiloride can prevent sodium retention and relieve nephrotic oedema in both rats, mice and humans. [5][6][7][8] As aldosterone is typically in normal range or suppressed in NS, possibly after a variable and short initial increase, the question is what activates ENaC in NS?…”
mentioning
confidence: 99%
“…There is substantial experimental evidence for the concept that proteolytic ENaC activation by proteasuria contributes to renal sodium retention in nephrotic syndrome . In particular, two key observations support this hypothesis: firstly, treatment with the ENaC inhibitor amiloride greatly attenuates renal sodium retention in rat and mouse models of nephrotic syndrome.…”
mentioning
confidence: 96%
“…In general, kinins induce a decrease in systemic blood pressure through stimulating natriuresis and diuresis in the kidney. Kallikreins are involved in ENaC regulation . Sodium retention in a rodent model of nephrotic syndrome is caused by activated serine proteases in the urine .…”
mentioning
confidence: 99%
“…Kallikreins are involved in ENaC regulation. 11 Sodium retention in a rodent model of nephrotic syndrome is caused by activated serine proteases in the urine. 12 Interestingly, kallikrein is detectable in the urine of proteinuric patients and capable of ENaC activation in vitro, suggesting a role in pathologic sodium retention.…”
mentioning
confidence: 99%